Bahasa Inggris - Deddi Fasmadhy Satiadharmanto (JURNAL PENDIDIKAN, 2023)
The discussion in this study is about how the Agenda Setting policy for general English courses in the transition period from the Covid 19 Pandemic to the Covid 19 Endemic At the Merdeka Learning Program - Merdeka Campus at the University of Tangerang Raya where English is an international language source which incidentally is related to a lot of information related to insight, science through written, print, electronic media as a source of information in communicating universally.The purpose of this research is how the Agenda Setting of the Independent Learning Policy - Merdeka Campus in the general English course lectures at the University of Tangerang Raya with a critical review of the Agenda Setting Deddi Fasmadhy.In addition, analyzing policies related to various obstacles encountered during lectures in the Merdeka Learning program – Merdeka campus.The method used in this study is a descriptive method with a qualitative approach.The results obtained from this research are that the distance learning method policy (PJJ) can produce good output. Students can take part in lectures properly supported and well prepared by the University of Tangerang Raya. For this research, we provide recommendations for problems that arise during lectures, so that the output of distance learning policies through online zoom or Google meet is the quality of learning is maintained, the quality is even increased in quality for all human resources involved in this online distance learning. . The weakness of students' comprehension is due to the limitations of online Zoom media, students are given individual assignments. It is hoped that the managerial lectures can improve the quality of superior English lectures,